THE EFFECTIVENESS OF DUOLINGO IN IMPROVING VOCABULARY MASTERY AMONG FOURTH-GRADE STUDENTS - Dadan Hidayat (Sekolah Tinggi Keguruan dan Ilmu Pendidikan Darud Da'wah Wal Irsyad Pinrang, 2025)
This study aims to investigate the effectiveness of the Duolingo application in enhancing vocabulary mastery among fourth-grade elementary school students. Many young learners struggle to retain new English vocabulary using conventional methods, highlighting the need for engaging and interactive digital tools. Using a pre-experimental one-group pre-test and post-test design, 20 students used Duolingo for vocabulary practice over four weeks, with eight sessions lasting approximately 45 minutes each. Data were collected through vocabulary tests before and after the intervention. The results show a significant increase in students’ post-test scores, indicating that Duolingo positively impacts vocabulary acquisition. This finding supports the integration of game-based digital tools into language instruction for young learners. Unlike previous studies that mostly focus on student perceptions or older learners, this study fills a clear research gap by providing empirical evidence of Duolingo’s measurable effect on vocabulary improvement in elementary students. This is novel because younger learners have different cognitive characteristics, requiring more visual, interactive, and repetitive activities to stay motivated and retain new words effectively. By testing Duolingo in this unique context with actual test scores, the study demonstrates that digital gamified learning can be both motivating and effective for primary students. The research contributes to the existing body of literature by emphasizing measurable vocabulary gains rather than perceptions alone.